Benchmark study of combustion model of premixed gas by using LBM - Л, Khenmedekh; Y, Obikane; E, Khatanbold (Scientific transaction of the National University of Mongolia. Physics, 2022)
The propane gas combustion in a combustor was calculated using a two-dimensional LBM method that used pressure, temperature, and the distribution function fp of chemical components: fT, fC3H8, fO2, fCO2, fN2, and fH2O. WOLFRAM MATHEMATICA was used in the calculation and three cases were calculated Case1: one dimension combustion flame of a uniform mixed gas (Re = 124) to obtain an average reaction rate omega; Case2: A twodimensional problem, without the influx, where ignition occurred in the center of the area; and Case3: calculate the combustion of the air-fuel mixture from fuel jets ejected from both upper and lower boundary. The flow field simulation area in the axial symmetry was 1/4. The shape of the flame front consisted of a curved surface, and then a nearly horizontal flame front was formed at the end of the simulation. For the one-dimensional case, the propagation speed was 0.25m/sec, which was larger than the results reported by Huidan Yue [9]. The flame propagation speed roughly matched that of the two-dimensional simulation by Yamamoto.